Flow-mediated interactions between two self-propelled flapping filaments in tandem configuration - Zhu, Xiaojue; He, Guowei; Zhang, Xing (Physical review letters, 2014)
The mechanism by which aggregates of active swimmers are formed is an intriguing problem. In this Letter we show that, for two tandem self-propelled filaments driven by harmonic plunging motions of identical frequency and amplitude, stable configurations can be spontaneously formed by locking the trajectories onto the vortex centers. Further analysis indicates that the grouping energetics is also dictated by the wake vortex structure. The rationale behind the energetic advantage of the follower is found to be the interplay among actuation, self-propulsion, and the vortical fluid environment.